Screening migrants for tuberculosis - a missed opportunity for improving knowledge and attitudes in high-risk groups: A cross-sectional study of Swedish-language students in Umeå, Sweden - Ahlm Clas; Hurtig Anna-Karin; Nkulu Faustine KK; Krantz Ingela (BMC, 2010)
Abstract Background Migrants from countries with a high-burden of tuberculosis (TB) are at a particular risk of contracting and developing the disease. In Sweden, new immigrants are routinely offered screening for the disease, yet very little is known about their beliefs about the disease which may affect healthcare-seeking behaviours. In this study we assessed recent immigrant students' knowledge of, and attitudes towards TB, and their relationship with the screening process. Methods Data were collected over a one-year period through a survey questionnaire completed by 268 immigrants consecutively registered at two Swedish-language schools in Umeå, Sweden. Participants originated from 133 different countries and their ages varied between 16-63 years. Descriptive and multivariate logistic regression analyses were then performed. Results Though most of them (72%) were screened, knowledge was in general poor with several misconceptions. The average knowledge score was 2.7 ± 1.3 (SD), (maximum = 8). Only 40 (15 %) of the 268 respondents answered at least half of the 51 knowledge items correctly. The average attitude score was 5.1 ± 3.3 (SD) (maximum = 12) which meant that most respondents held negative attitudes towards TB and diseased persons. Up to 67% lacked knowledge about sources of information while 71% requested information in their vernacular. Knowledge level was positively associated with having more than 12 years of education and being informed about TB before moving to Sweden. Attitude was positively associated with years of education and having heard about the Swedish Communicable Disease Act, but was negatively associated with being from the Middle East. Neither knowledge nor attitude were affected by health screening or exposure to TB information after immigration to Sweden. Conclusions Though the majority had contact with Swedish health professionals through the screening process, knowledge about tuberculosis among these immigrants was low with several misconceptions and negative attitudes. Information may currently be inaccessible to most of these immigrants due to the language barrier and unfamiliarity with the Swedish healthcare system. If TB education was included as a component of screening programmes, ensuring that it was tailored to educational background, addressed misconceptions and access problems, it could well help improve TB control in these communities.